Effect of Pulmonary Rehabilitation for Patients With Post-COVID-19: A Systematic Review and Meta-Analysis - Chen, Huan; Shi, Hangyu; Liu, Xitong; Sun, Tianheng; Wu, Jiani; Liu, Zhishun (Frontiers in Medicine, 2022)
Background: evidences increasingly suggested that impaired respiratory function remained in about 40% of Coronavirus disease 2019 (COVID-19) patients after discharge, jeopardizing their activities of daily living and quality of life (QoL) in a long-term. Pulmonary rehabilitation (PR) can improve exercise capacity and QoL in individuals with chronic lung disease, however, evidence on PR’s effect for post-COIVD-19 patients was scarce. This study aims to conduct a systematic review and meta-analysis to evaluate the effect of PR on lung impairment for post-COVID-19 patients. Methods: five databases were searched for all published trials of PR for post-COVID-19 patients from 2019 to Oct 2021. Data was extracted using standardized form. Risks of bias of included studies were assessed using Cochrane risk of bias assessment tool. Data was synthesized where possible, otherwise, qualitative analysis was done. Results: among 6000 retrieved studies, 3 studies with 233 patients after COVID-19 were included. The pooled estimate of PR effect on 6-MWT (50.41, 95%CI 34.34 to 66.48; P<0.0001) was in favor of experiment group with clinical importance. It’s found that PR could improve symptom of dyspnea and quality of life results, however, its effects on pulmonary function test were inconsistent across studies. The risk of bias of included studies varied, with major concerns on risk of blinding of participants and interventions performers. Conclusion: the review showed that PR could improve exercise capacity measured by 6-MWT among patient with mild to moderate lung impairment after COVID-19. The interpretation of effects on lung function, dyspnea and QoL should be cautious due to inadequate and conflicting data reported across studies.